سلوك التدخين عند الشباب و علاقته بكل من مصدر الضبط و استراتيجيات المواجهة -دراسة حسب نموذج علم نفس الصحة- - كريمة, سي بشير; حليمة, لعوج (Sciences de l'Homme et de la Société, 2017)
الملخص: إن مشكلة التدخين لدى الشباب يعتبر من مشكلات الصحة العامة حيث يعتبر التدخين من الاسباب الرئيسية للوفاة في العالم اليوم ، كما أنه أحد عوامل الخطر للأسباب الرئيسية الثمانية للوفاة في العالم فهو يسبب سرطان الرئة والحنجرة والكلى والمثانة والمعدة والقولون وتجويف الفم والمريء، وسرطان الدم، التهاب الشعب الهوائية المزمن، ومرض الانسداد الرئوي المزمن وأمراض القلب الدماغية و الحوادث الدماغية الوعائية، والإجهاض والولادة المبكرة والتشوهات الخلقية والعقم، مسببا معاناة إنسانية التي كان من الممكن تجنبها .ومن هنا جاء البحث الحالي لدراسة العلاقة بين سلوك التدخين و مركز الضبط من جهة و سلوك التدخين و استراتيجيات المواجهة من جهة اخرى عند عينة تتكون من خمسين شابا تتراوح اعمارهم بين 22 و 53 عاما. Abstract: Youth smoking is a top notch public health issue and the leading preventable cause of death in the world today and is one of the world's eight leading causes of death worldwide. Tobacco smoking causes, among others, cancers of the lung, larynx, kidney, bladder, stomach, colon, oral cavity and esophagus, leukemia, chronic bronchitis, chronic obstructive pulmonary disease, heart disease ischemic, stroke, miscarriage and premature birth, congenital anomalies and infertility, causing human suffering that could be avoided and sacrificing many years of life. The literature review reports a lack of research on smoking behavior among young adults in relation to other variables. Where the current research to study the link between smoking behavior and the place of control of a part and and smoking behavior and coping strategies on the other hand, in a sample of 50 young people aged between 22 and 35 years old.